If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 + 5 + (x + 8) = 0 Reorder the terms: 4x + -4 + 5 + (8 + x) = 0 Remove parenthesis around (8 + x) 4x + -4 + 5 + 8 + x = 0 Reorder the terms: -4 + 5 + 8 + 4x + x = 0 Combine like terms: -4 + 5 = 1 1 + 8 + 4x + x = 0 Combine like terms: 1 + 8 = 9 9 + 4x + x = 0 Combine like terms: 4x + x = 5x 9 + 5x = 0 Solving 9 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 0 + -9 5x = 0 + -9 Combine like terms: 0 + -9 = -9 5x = -9 Divide each side by '5'. x = -1.8 Simplifying x = -1.8
| 10+0.25(200)=X | | 8+7m=m-4 | | 10-(x-7)+2x=5 | | r^2-3=2r | | 2=-2b-8 | | -17+3(.25)=x | | 6n-3=4+5n | | 4g=5 | | X^2+5x-24=-6+2x | | 10+X=-30 | | (X+6)(X-8)(2x-7)=0 | | -8(t+9)=6 | | 3x-1+4x+3=180 | | 5b^2+31b+30=0 | | y^2-4x^2=16 | | 6=7s-4 | | 2+2p=2-2p | | 1.82=Log(x) | | 2(-4)-3=x | | 5x+4=6x-42+8 | | 7+m=6 | | 2p+4p-7x+3=4p+5-3x | | -5x-6=-1 | | V^2-2v-5=-3v-3 | | 12x-8=15x-14 | | -5(x-3)=5(x-3) | | 5m+3n-2m-8n= | | (x+2)(7x+8)=0 | | 9-4+5h+3x= | | 9x/2=3x | | 9-4+53+32= | | 25c^2-121g^2=0 |